Reviews Simile in the Ruh-alarvah of Shahaboddin Ahmad Samaani with emphasis on the vehicle - hamid rezaie; محمد رضایی; منیره مسیبی (مطالعات زبانی و بلاغی)
Simile is as the most widely used means in Ruh-aharvah that the author has used it to explain his ideas and his thoughts. Most similes of Ruh-aharvah are of kind of reasonable to sensible and also of eloquent which is used for additional simile. Since, vehicle of the elements of simile has most roles in expressing the author's worldview, this paper with an emphasis on this element is paid to analyze the similes in Ruh-alarvah and has determined that Samaani is considered the use of reasonable to sensible simile and using natural elements as vehicle as the best practices in mystical concepts and explaining mystic moods and circumstances and his officials. Material of vehicle in Ruh-alarvah is diversified. But the nature is the most important subject that the author considered in his illustration. Of total of 2640 review similes, number 636 is related to nature and its elements. Then living devices, clothing and different locations have been used as vehicle. Martial of art terms, animals, humans, human organs, jewelry and mining, light, businesses and food are placed in the next category.